2023
DOI: 10.3390/cells12030486
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Ketone Body, D-β-Hydroxybutyrate, on Sirtuin2-Mediated Regulation of Mitochondrial Quality Control and the Autophagy–Lysosomal Pathway

Abstract: Mitochondrial activity and quality control are essential for neuronal homeostasis as neurons rely on glucose oxidative metabolism. The ketone body, D-β-hydroxybutyrate (D-BHB), is metabolized to acetyl-CoA in brain mitochondria and used as an energy fuel alternative to glucose. We have previously reported that D-BHB sustains ATP production and stimulates the autophagic flux under glucose deprivation in neurons; however, the effects of D-BHB on mitochondrial turnover under physiological conditions are still unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 70 publications
1
16
0
Order By: Relevance
“…Therefore, butyrate‐related treatments, or exploiting the gut microbiome to increase butyrate production, may have therapeutic potential for SCA3. While not explored within a SCA3 model, a recent study found that placing healthy mice on a ketogenic (low carbohydrate, high fat) diet resulted in increased levels of D‐β‐hydroxybutyrate in the blood and activation of the autophagy pathway 79 . Further, combined treatment of taurursodiol, a soluble form of bile acid, and phenylbutyrate, a derivative of butyric acid, has been found to improve survival in clinical cohorts of ALS patients 41 and received FDA approval for the treatment of ALS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, butyrate‐related treatments, or exploiting the gut microbiome to increase butyrate production, may have therapeutic potential for SCA3. While not explored within a SCA3 model, a recent study found that placing healthy mice on a ketogenic (low carbohydrate, high fat) diet resulted in increased levels of D‐β‐hydroxybutyrate in the blood and activation of the autophagy pathway 79 . Further, combined treatment of taurursodiol, a soluble form of bile acid, and phenylbutyrate, a derivative of butyric acid, has been found to improve survival in clinical cohorts of ALS patients 41 and received FDA approval for the treatment of ALS.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the FOXO family of transcription factors has been reported to have pro‐longevity effects 75,76 and are reported to be downregulated with aging, 77 suggesting a potential benefit of FOXO1‐related therapeutics in age‐linked neurodegenerative diseases 78 . Most recently, it has been demonstrated that treatment with ketone body, D‐β‐hydroxybutyrate, can activate the autophagy pathway through the AMPK pathway and activate transcription factors FOXO1 and FOXO3a in healthy rat cortical neurons 79 . Previously, overexpression of DAF‐16, the equivalent gene of FOXO in C. elegans , prevented motor impairment in a C. elegans model of SCA3 80 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Intermittent fasting remains promising, as it improved behavioral performance and neuronal survival at the injured segment after spinal cord injury, which was prevented with autophagy inhibition, and exerted neuroprotective effects after TBI [127,128 ▪ ]. Ketone bodies, which rise upon fasting, stimulate autophagy [126,129]. However, protection against sepsis-induced muscle weakness with ketone-bodies infusion appeared not mediated via autophagy stimulation [130].…”
Section: Nutrition and Autophagy Deficiency In Critical Illnessmentioning
confidence: 99%
“…Indeed, β-hydroxybutyrate (BHB), the main ketone body produced in a KD, has a relevant influence on hallmarks of aging as it reduces the production of reactive oxygen species (Shimazu et al 2013), enhances cell proteostasis (Finn and Dice 2005), activates mitochondrial biogenesis (Hasan-Olive et al 2019), and prevents cell senescence (Han et al 2018) and inflammation (Youm et al 2015). Moreover, ex vivo and in vitro studies indicate that ketone bodies counteract neuronal hyperexcitability (Kadowaki et al 2017), stimulate Aβ 1-40 clearance (Versele et al 2020) and activate autophagy in cortical neurons (Gomora-García et al 2023). Additionally, the administration of ketone esters as an alternative way to deliver ketone bodies to the brain, improves cognition in humans (Fortier et al 2021).…”
Section: Introductionmentioning
confidence: 99%